Step‐by‐Step Design and Synthesis of Au@SiO2@Phenyl‐azathiacrown for SERS‐Based Specific Quantification of Inorganic Mercury. Issue 2 (1st March 2017) - Wu, Yuchao; Yang, Limin; Wang, Qiuquan
Abstract: Direct SERS‐based quantification of inorganic metal species has been a problem, because they have a small Raman cross‐section or even no vibrational mode. Here, we report a new strategy for SERS‐based quantification of such metal species, as exemplified by inorganic mercury (Hg II ) in waters. Step‐by‐step design and synthesis from azathioethers [3, 9‐dithia‐6‐monoazaundecane (DMA) and 3, 6, 12, 15‐tetrathia‐9‐monoazaheptadecane (TTM)] to an azathiacrown [7‐aza‐1, 4, 10, 13‐tetrathiacyclohexadecane (NS4)] demonstrate an improved S‐pulling effect and size‐fit specificity towards Hg II to form Hg−S bonds. Modification of NS4 on the surface of Au@SiO2 by using a 4‐(bromomethyl)benzoic linker enabled direct SERS‐based specific quantification of Hg II for the first time, in which the ultrathin layer (ca. 2 nm) that covered the Au core (55 nm) could be a barrier preventing the Au core from having direct interaction with the Hg II, and with phenyl serving as an internal standard (IS). The ratio of the Hg−S SERS band intensity at 270 cm −1 to that of IS [( γ CC+ γ CCC) at 1046 cm −1 ] was practically proportional to the concentration of Hg II, eliminating the inevitable uncertainties encountered in SERS‐based measurements. Such a methodology is expected to pave a new way for SERS‐based quantification of inorganic metal species when specific complexing substrates and suitable ISs are designed. Abstract : Waterworks : Direct surface‐enhanced Raman scattering (SERS)‐based quantification of inorganic metal species is problematic, because they have a small Raman cross‐section or even no vibrational mode. An Au@SiO2 @phenyl‐azathiacrown SERS substrate is developed for quantification of such metal species, as exemplified by inorganic mercury (Hg II ). Size‐fit and S‐pulling effects of azathiacrown linked by phenyl on Au@SiO2 nanoparticles allow us to perform a direct, sensitive, and specific quantification of Hg II in various waters.